She Doesn’t Even Go Here: The Role of Inflammatory Astrocytes in CNS Disorders - Reid, Jacqueline Kelsey; Kuipers, Hedwich Fardau (Frontiers in Cellular Neuroscience, 2021)
Astrocyte heterogeneity is an evolving field, rapidly driven by innovative techniques. Inflammatory astrocytes, one of the first described subtypes of reactive astrocytes, are present in a variety of neurodegenerative diseases and may play a role in their pathogenesis. Moreover, genetic and therapeutic targeting of these astrocytes ameliorates disease in several models, providing support for advancing the development of astrocyte-specific disease modifying therapies. This review aims to explore the methods and challenges of identifying inflammatory astrocytes, the role these astrocytes play in neurodegenerative diseases, and the future directions in the field of astrocyte heterogeneity.